2022
DOI: 10.1186/s12875-022-01891-9
|View full text |Cite
|
Sign up to set email alerts
|

Experimental system of care coordination for the home return of patients with metastatic cancer: a survey of general practitioners

Abstract: Background To promote improved coordination between general practice and hospital, the French clinical trial CREDO (“Concertation de REtour à DOmicile”) is testing an innovative experimental consultation for patients with metastatic cancer who are returning home. This consultation involves the patient, the patient’s referring GP (GPref) and a GP with specific skills in oncology (GPonc) in a specialized care center. The objective of our study is to explore the satisfaction of GPsref about this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…It's so complex, the third antibody or the third checkpoint-inhibitor for lung cancer, I don't know it." [ GP 10,33] Because of the knowledge gap it is di cult for GPs to determine the risk-bene t ratio or to decide on the end of a cancer treatment. The rapid changes in oncological treatment options may even lead to avoidance of talking about prognosis and EOL at all.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It's so complex, the third antibody or the third checkpoint-inhibitor for lung cancer, I don't know it." [ GP 10,33] Because of the knowledge gap it is di cult for GPs to determine the risk-bene t ratio or to decide on the end of a cancer treatment. The rapid changes in oncological treatment options may even lead to avoidance of talking about prognosis and EOL at all.…”
Section: Resultsmentioning
confidence: 99%
“…Normally I follow the hospital's recommendations." [ GP 3,33] On the other hand, some situations seem problematic when opinions about treatment goals differ. Some GPs choose patient-empowerment as a strategy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve interdisciplinary collaboration, studies implementing new strategies have shown some success: e.g. remote participation of GPs in multi-disciplinary meetings at the cancer center or integrating GPs with speci c oncological skills in the center before the home return of patients [33,34]. Still, review of the literature shows that the direct oral communication during the active phase of cancer treatment should be further developed [35].…”
Section: Discussionmentioning
confidence: 99%